The Contribution Of Kiai Munawwar Adnan Kholil Gresik On Islamic Education - Ma'arif, Muhammad Anas; Nabila, Nur Silva (Tribakti: Jurnal Pemikiran Keislaman, 2020)
Pesantren as an indigenous culture is able to create unique traditions and works. The creation of a pesantren is caused by the persistence of its founder, the Kiai. The pesantren will remain an educational reference if the pesantren system and management are well managed. The importance of conducting narrative research from Kiai Munawwar is because of his expertise in managing education and creating works in many fields of science. And this has not been much written about the Kiai Munawwar. This study uses philosophical historical research by narrating the characters, works, and biography and analyzing their contribution to Islamic education. This research resulted in: 1) Kiai Munawwar made a maximum contribution in Gresik through formal, non-formal education and life skills education for his students. 2) the works that have been written can be used as a pesantren education curriculum 3) life skill education as a means of (khidmah) in the pesantren. 4) The aim of pesantren education is by forming ulama and, generous tycoons 5) Educational methods by telling stories (history). Recommendation: Future research can examine Kiai Munawwar's works from various perspectives or in-depth biographical research.